Benefits of Common Bean Intercropping with Maize are Independent of Altitudinal Gradients in the Northern Highlands of Tanzania - Eliakira Kisetu Nassary (Current Research Progress in Agricultural Sciences Vol. 8, 2025)
Common bean (Phaseolus vulgaris L.) is an important crop for smallholder farmers, providing both food and income. However, its potential benefits when intercropped with maize (Zea mays L.) remain underutilized. This study assessed the productivity of common bean intercropped with maize at different altitudes in the northern highlands of Tanzania over two cropping seasons (2015 and 2016). The study was conducted at three altitudes: lower (843 m), middle (1051 m), and higher (1743 m) above sea level, comparing sole cropping and intercropping practices. Bean and maize yields were measured, and the Land Equivalent Ratio (LER) was calculated. Results showed that intercropping increased bean grain yields from 1.5 to 2.3 t ha-1 at lower altitudes, 2.0 to 2.3 t ha-1 at middle altitudes, and 1.8 to 2.9 t ha-1 at higher altitudes. Cropping season, altitude, and cropping practice all significantly affected bean yields, with the onset of rains differing by altitude—March/April for the lower and middle altitudes, and September for the higher altitude. The total LER for intercropping was 1.58, while the partial LER for beans was 1.53. No significant differences in LER were observed across altitudes, indicating that the benefits of intercropping are not altitude-specific. These findings suggest that intercropping is an effective practice for enhancing productivity across varying altitudes in the region.